Geo-mechanics and Hydraulic Conductivity Study of Claystone in Boyolali, Central Java, Indonesia - Wawan Budianta; Monika Aprianti Popang; Widyawanto Prastistho; Jiro Takemura (Geological Engineering Department Universitas Gadjah Mada, 2019)
Claystone middle Miocene age were found in Wonosegoro sub-district, Boyolali region, Central Java, Indonesia. The purpose of the paper is to examine and discuss the geology and typical behavor of this claystone and its micro-level mechanism. The hydraulic conductivity was assessed using consilidated apparatuses; 150 mm diameter column mound using aggregated sample and 60 mm oedometer mould using slurry sample as a reference. Claystone materials used were treated under various conditions. In long term test under constand vertical stress and hydraulic gradient, the hydraulic conductvity decreases with time although the volume of void volume of the sample increased by swelling. Water contens of the individul aggregated increased by swelling, by which strength of particles decreases with and aggregate breakdown was enchanced. As a result, large void created by large particles could be redused in its size, leading the reduction of hydraulic conductuvity. The hydralic conductivities (K values) obtained from the aggregated sample varied in a broad range compared with those from slurry sample. In the test using the higher percentage of gravel-sized aggregate (up until couarse gravel-sized; retained in 26.5 mm sieve), K values changed from 10-5 to 10-7 m/s under vertical stresses from 5 up to 245 kPa. The test was repeated using smaller percentage of gravel-sized aggregate (up until fine gravel-sized, retained in 4.75 mm sieve) and the observed K values changed from 10-5 to 10-10 m/s. While the K values obtained in the specimen made from surry under same vertical stresses was 10-9 to 10-11 m/s. All of the extruded aggregate samples had higher water content than the initial ones, which suggest the alteration mechanism of soled consolidation phase to more deformable plastic phase, whice enables thesample to decrease the void size. These results conclude that using coarse gravel-sized aggregated, which is a reasonable scenario of a practically feasible aggregate size in a field, may noy produce the aimed hydraulic conductivity by the regulated standard. Therefore, breakdown of the aggrgate size and enchament of swelling are crucial factors for the application of the clay stones as a barrier material.